Microstructure, mechanical behavior, and wear properties of FeCrMoVC steel prepared by selective laser melting and casting. (1st January 2017) - Sander, J.; Hufenbach, J.; Giebeler, L.; Bleckmann, M.; Eckert, J.; Kühn, U.
Graphical abstract: